Impugnación de acuerdos negativos. Comentario a la Sentencia núm. 218/2024 de la Audiencia de Valencia de 24 de septiembre - Pastor Martínez, Eduardo (2024)
The purpose of this work is the presentation of the recent Judgment of the Provincial Court of Valencia no. 218 of September 24, 2024, in which, with an analysis of the doctrine and jurisprudence on the matter, the challenge of the so-called negative agreements in the framework of capital companies is addressed, and the scope of the resolutions of the Courts from the perspective of complementing, or not, the corporate will. These notes are framed in the context of other doctrinal comments on rulings on challenging negative agreements (such as that of the Madrid Court of June 24, 2022, or that of the Italian Court of Cassazione of March 22 of 2024) to highlight the judicial contributions on the issue.